Application of Weighted Product (WP) Method in Decision Support of Unmer Madiun Rector Election - Pradityo Utomo; Arief Budiman (RESEARCH : Journal of Computer, Information System & Technology Management, 2020)
Universitas Merdeka Madiun (UNMER Madiun) is a private campus in Madiun, East Java, led by a Chancellor. The Chancellor served for four years. Prospective Chancellors choose through Senate consideration. The selection parameters include Curriculum Vitae, Vision and Mission, and Feasibility Test. In giving attention, debates often occur in Senate meetings. Based on this, this study created a system based on information technology that can help in making decisions. Decision Support System made using the Weighted Product method. Because in terms of computing time is faster than other SPK methods, so it is faster in making decisions. The criteria used to determine decisions using the assessment parameters used in the 2019 Chancellor election. The flow of this research starts from the stage of data collection, library research, making a decision support system, and testing the system. At the stage of data collection, it was done by collecting secondary data such as the parameter parameters in the selection of the Chancellor, which then is used for the criteria data. Furthermore, in making decision support systems using prototyping system development methods. After the system is created, the system tested. For the results of this study have been successfully applied Weighted Product method to support the decision of the Chancellor selection. Furthermore, the system that has tested using the BlackBox method evaluates the success of the system. Based on the results of system testing, the success rate of SPK that has made 100% successful results.